INTEGRATED EFFECTS OF AZOLLA INCORPORATION AND INTERCROPPING ON RICE GROWTH, AND BIOMASS NUTRITIONAL VALUE - Putu Oki Bimantara; I Made Adnyana; Ni Gusti Ketut Roni (Universitas Veteran Bangun Nusantara, 2026)
The excessive reliance on chemical fertilizers in rice cultivation has raised concerns regarding environmental sustainability and nutrient inefficiency, highlighting the need for alternative biofertilizer strategies. Although Azolla has been widely studied, most studies have focused primarily on soil properties without integrating crop performance and biomass utilization. This study aimed to evaluate the integrated effects of Azolla incorporation and intercropping on rice growth, nitrogen uptake, and the nutritional value of Azolla biomass. A greenhouse experiment was conducted using a completely randomized design with eight treatments and three replications, including control (no Azolla), Azolla incorporation at 240, 280, and 320 g/pot with and without intercropping, and chemical fertilizer treatment. The results showed that Azolla application significantly improved rice growth parameters, with plant height, leaf number, and tiller number increasing by up to 15–30% compared to the control. Higher Azolla doses (320 g/pot) consistently produced the best performance. In addition, Azolla biomass exhibited high nutritional value, with crude protein content exceeding 20%, suggesting its potential as a supplementary livestock feed. These findings demonstrate that Azolla can function as a multifunctional bioresource, enhancing crop performance while supporting biomass valorization within integrated agricultural systems. Keywords: Azolla, biomass utilization, nitrogen uptake, rice growth, sustainable agriculture